Managerial accounting - Whitecotton, Stacey (McGraw-Hill/Irwin, 2011)
Introduction to managerial accounting -- Job order costing -- Process costing -- Activity-based costing and cost management -- Cost behavior -- Cost-volume-profit analysis -- Incremental analysis for short-term decision making -- Budgetary planning -- Standard costing and variances -- Decentralized performance evaluation -- Capital budgeting -- Statement of cash flows -- Measuring and evaluating financial performance -- Glossary -- Check figures -- Answers to multiple-choice -- Questions -- Credits -- Index.